Close genetic connectivity of soft coral Sarcophyton trocheliophorum in Indonesia and its implication for marine protected area - Aradea Bujana Kusuma; Dietrich Geoffrey Bengen; Hawis Madduppa; Beginer Subhan; Dondy Arafat; Bertoka Fajar S.P. Negara (Aceh Journal of Animal Science, 2016)
The genetic connectivity of soft coral is influenced by current and distance between islands. The complexity of islands and geographical region in Indonesia might influence the distribution of soft corals.  The information of genetic connectivity can be used to design marine protected areas and to avoid destruction and possible extinction. The objective of the present study was to analyze genetic connectivity of one species of soft coral, Sarcophyton trocheliophorum, in three populations spanning Java, Nusa Tenggara, and Sulawesi’s waters, and to describe its implication for marine protected area. The mitochondrial protein-coding gene (750 bp of ND2) was used to analyze genetic population structure and genetic connectivity. Genetic connectivity was found in all populations with Fst value of 0.227 to 0.558, indicating populations had the close genetic relationship. The local and Indonesian currents were expected to distribute the larva to islands as a stepping stone, they moved slowly to spread them self far away. Tanakeke island (Sulawesi population) might be a center connectivity of S. trocheliophorum populations. This island connected with islands in west and east Indonesia, therefore that area need to protect